A crítica de arte no Brasil em fins do século XIX e início do XX: Gonzaga Duque e Angyone Costa - Mendonça, Aureo Guilherme (1998)
The following dissertation was conceived from certain signs emitted by publications about the history of the art which alerted to the specifity of some works by artists from the crossing of the century, who already signalled a production independent from academic formalism. This modernity was being tirelessly built by Gonzaga Duque’s critical work, whose analyses were always accompanied by his pioneer view as to what the destiny of brazilian art shuold be. In our study we tried to contextualize Gonzaga Duque’s work, mentioning those statements we felt that most faithfully show this behavior and so are able to explicit his aesthetic feeling. To accompany him we have indued Angyone Costa’s work, who also developed a criticism poiting to the search of the new in our art and to accomplish his task he not only gave opinions about the artistic production of this time, but also wanted to hear the artists thenselves and what they thought of their works. Organizing this multiplicity of views, searching in the various treatments given to the matter of the art those points which seemed to manifest the search of the new, was our most important task in this study. To deepen still scattered notions about that moment of our artistic performance a little more, revealing qualities which seemed to hide under the set of ideas of the modernism of the 20’s, is what seems to us the result gotten with the present research. We hope to have advanced a little more in the task of rethinking the modernism as part of a major process and which would have involved more than a scenary with the presence of actors not included in the official cast so far. Stirring our history of the art, amplifying the i possibilities of understanding it’s course, and verifying the roles of the involved charaters was our way of giving new dimensions to some then scattered matters, granting tnem a new look, closer to their real meanings.